Stereoelectronic Chameleons: The Donor–Acceptor Dichotomy of Functional Groups - Vatsadze, Sergey Z.; Loginova, Yulia D.; dos Passos Gomes, Gabriel; Alabugin, Igor V. (Chemistry : a European journal, 2017)
Stereoelectronic factors account for the apparent reversal of donor–acceptor properties of a variety of functional groups by a simple change of their orientation in space. The new reactivity patterns that arise from spatial anisotropy are associated with chameleonic behavior of common organic functionalities. CHEMeleon: Stereoelectronic factors account for the apparent reversal of donor–acceptor properties of a variety of functional groups by a simple change of their orientation in space. The new reactivity patterns that arise from spatial anisotropy are associated with chameleonic behavior of common organic functionalities.